Correction: Khavinson et al. Neuroprotective Effects of Tripeptides—Epigenetic Regulators in Mouse Model of Alzheimer’s Disease. Pharmaceuticals 2021, 14, 515 - Vladimir Khavinson; Anastasiia Ilina; Nina Kraskovskaya; Natalia Linkova; Nina Kolchina; Ekaterina Mironova; Alexander Erofeev; Michael Petukhov (Pharmaceuticals)
In the original publication [...]